THE USE OF BAYES METHOD TO DIAGNOSE GESTATIONAL DIABETES IN PREGNANT WOMEN (CASE STUDY: DR. EDWARD JOB,. SP.OG) - Maulidina, Nadia; Simanjuntak, Magdalena; Maulita, Yani (Journal of Mathematics and Technology (MATECH), 2024)
Gestational Diabetes is the cause of diabetes that occurs during pregnancy, generally, this pregnancy occurs in the second trimester, between Weeks 24 to 28. Gestational Diabetes is one of the causes of death of pregnant women due to lack of information or knowledge about the factors that cause gestational diabetes that occurs in mothers during pregnancy, causing health risks, and affect the decision of time, cost and others in carrying out direct medical consultations. Therefore, it is highly recommended that an expert system for treating gestational diabetes in pregnant women be able to find out early about what is happening and be able to overcome the causes and reduce mortality. With the existence of this system is expected to be an alternative for patients who experience complications of time, cost and others in consulting directly about the treatment of gestational diabetes in pregnant women, before coming directly to meet with a doctor/expert. From the process using the Bayes method above, it is explained that the diagnosis of gestational diabetes in pregnant women is diagnosed with gestational diabetes Diabetes Mellitus (P01) with a percentage of 90.73%.